How many people will need palliative care in Scotland by 2040? A mixed-method study of projected palliative care need and recommendations for service delivery. Issue 2 (3rd February 2021) - Finucane, Anne M; Bone, Anna E; Etkind, Simon; Carr, David; Meade, Richard; Munoz-Arroyo, Rosalia; Moine, Sébastien; Iyayi-Igbinovia, Aghimien; Evans, Catherine J; Higginson, Irene J; Murray, Scott A
Abstract : Objective: To estimate future palliative care need and complexity of need in Scotland, and to identify priorities for future service delivery. Design: We estimated the prevalence of palliative care need by analysing the proportion of deaths from defined chronic progressive illnesses. We described linear projections up to 2040 using national death registry data and official mortality forecasts. An expert consultation and subsequent online consensus survey generated recommendations on meeting future palliative care need. Setting: Scotland, population of 5.4 million. Participants: All decedents in Scotland over 11 years (2007 to 2017). The consultation had 34 participants; 24 completed the consensus survey. Primary and secondary outcomes: Estimates of past and future palliative care need in Scotland from 2007 up to 2040. Multimorbidity was operationalised as two or more registered causes of death from different disease groups (cancer, organ failure, dementia, other). Consultation and survey data were analysed descriptively. Results: We project that by 2040, the number of people requiring palliative care will increase by at least 14%; and by 20% if we factor in multimorbidity. The number of people dying from multiple diseases associated with different disease groups is projected to increase from 27% of all deaths in 2017 to 43% by 2040. To address increased need and complexity, experts prioritised sustained investment in a national digital platform, roll-out of integrated electronic health and social care records; and approaches that remain person-centred. Conclusions: By 2040 more people in Scotland are projected to die with palliative care needs, and the complexity of need will increase markedly. Service delivery models must adapt to serve growing demand and complexity associated with dying from multiple diseases from different disease groups. We need sustained investment in secure, accessible, integrated and person-centred health and social care digital systems, to improve care coordination and optimise palliative care for people across care settings.